Elderly well being physical system - Ng, Xin Yi (Nanyang Technological University, 2022)
COVID-19 has had profound impacts on our lives in different ways, with one of them being a high demand for physiotherapists and other healthcare workers during the pandemic. This has resulted in a lack of manpower to guide the elderly in their regular physiotherapy sessions. A desirable solution to the problem would have the elderly receiving the required guidance for their exercises while reducing the workload for physiotherapists.